Physiological effects and subjective tolerability of prone positioning in COVID-19 and healthy hypoxic challenge. Issue 1 (7th February 2021) - Jha, Akhilesh; Chen, Fangyue; Mann, Sam; Shah, Ravi; Abu-Youssef, Randa; Pavey, Holly; Lin-Jia-Qi, Helen; Cara, Josh; Cunningham, Daniel; Fitzpatrick, Kate; Goh, Celine; Ma, Renee; et al.
Background: Prone positioning has a beneficial role in coronavirus disease 2019 (COVID-19) patients receiving ventilation but lacks evidence in awake non-ventilated patients, with most studies being retrospective, lacking control populations and information on subjective tolerability. Methods: We conducted a prospective, single-centre study of prone positioning in awake non-ventilated patients with COVID-19 and non-COVID-19 pneumonia. The primary outcome was change in peripheral oxygenation in prone versus supine position. Secondary outcomes assessed effects on end-tidal CO2, respiratory rate, heart rate and subjective symptoms. We also recruited healthy volunteers to undergo proning during hypoxic challenge. Results: 238 hospitalised patients with pneumonia were screened; 55 were eligible with 25 COVID-19 patients and three non-COVID-19 patients agreeing to undergo proning – the latter insufficient for further analysis. 10 healthy control volunteers underwent hypoxic challenge. Patients with COVID-19 had a median age of 64 years (interquartile range 53–75). Proning led to an increase in oxygen saturation measured by pulse oximetry ( S pO2 ) compared to supine position (difference +1.62%; p=0.003) and occurred within 10 min of proning. There were no effects on end-tidal CO2, respiratory rate or heart rate. There was an increase in subjective discomfort (p = 0.003), with no difference in breathlessness. Among healthy controls undergoing hypoxic challenge, proning did not lead to a change in SpO2 or subjective symptom scores. Conclusion: Identification of suitable patients with COVID-19 requiring oxygen supplementation from general ward environments for awake proning is challenging. Prone positioning leads to a small increase in S pO2 within 10 min of proning though is associated with increased discomfort. Awake prone positioning in patients with #COVID19 causes a small increase in S pO2 within 10 min of proning but is associated with increased subjective discomfort, and challenges in the identification of hospital patients suitable for the procedure https://bit.ly/3wg84BC